2013
DOI: 10.1186/1471-2458-13-456
|View full text |Cite
|
Sign up to set email alerts
|

Burden of self-reported acute gastrointestinal illness in China: a population-based survey

Abstract: BackgroundAcute gastrointestinal illness (AGI) is an important public-health problem worldwide. Previous national studies of the incidence of AGI in China were performed decades ago, and detailed information was not available. This study therefore sought to determine the magnitude, distribution, and burden of self-reported AGI in China.MethodsTwelve-month, retrospective face-to-face surveys were conducted in 20 sentinel sites from six provinces between July 2010 and July 2011.ResultsIn total, 39686 interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
63
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 35 publications
(44 reference statements)
14
63
4
Order By: Relevance
“…We found that ≈4 in 100 persons reported having diarrhea in the previous month prior to the interview and that ≈1 in five individuals with diarrhea reported seeking healthcare during their most recent episode of diarrhea. The estimated incidence rate of diarrhea in Pudong was 0·54 episodes per person-year, which is very close to the 2010 national estimate of 0·56 episodes per personyear [5]. These findings confirm that the rate of diarrhea has not changed substantially over the past couple of years and that the burden of diarrhea experienced by the community and healthcare facilities is substantial in Pudong.…”
Section: Discussionsupporting
confidence: 71%
“…We found that ≈4 in 100 persons reported having diarrhea in the previous month prior to the interview and that ≈1 in five individuals with diarrhea reported seeking healthcare during their most recent episode of diarrhea. The estimated incidence rate of diarrhea in Pudong was 0·54 episodes per person-year, which is very close to the 2010 national estimate of 0·56 episodes per personyear [5]. These findings confirm that the rate of diarrhea has not changed substantially over the past couple of years and that the burden of diarrhea experienced by the community and healthcare facilities is substantial in Pudong.…”
Section: Discussionsupporting
confidence: 71%
“…None of these studies have collected comprehensive information regarding childhood infections and vaccinations, as well as the development of the infants' microbiome when investigating the development of the immune system and diseases in later life. As more than half of the acute respiratory infections (ARI) and one quarter of the gastrointestinal infections in childhood do not lead to a consultation of a physician [9][10][11][12][13], recording the complete history of infections during childhood can be aided by assistance from the parents in conducting daily observations regarding symptoms and obtaining biomaterials during infection episodes. In a similar fashion, the assessment of changes of the nasal and the gut microbiome over time and in relation to infections and the development of immunity requires regular collection of nasal swabs and stool samples during asymptomatic episodes, which also can be aided by parents' assistance.…”
Section: Introductionmentioning
confidence: 99%
“…Either approach would be too expensive with respect to both personal and financial resources for a long-term collection of bio samples in a large birth cohort in Germany with the goal of capturing the entire history of infections. If a sample collection was only conducted during hospital visits or consultation of a physician, more than half of the respiratory infections and one quarter of the gastrointestinal infections in childhood would be missed [9][10][11][12][13]. Sending study staff to pick up the samples from the homes of the participants is very resource intensive and not necessary in Germany as, in contrast to Australia, bio samples can be sent by standard mail.…”
Section: Introductionmentioning
confidence: 99%
“…In England and Wales, foodborne gastroenteritis caused an estimated 2.4 million illnesses, 21138 hospitalizations, and 718 deaths in 1995 (Adak, Long, & O'Brien, 2002). A study of acute gastrointestinal illness (AGI) in China estimated 209 million episodes of foodborne disease occurred in 2010e2011, and the relative incidence in China appears to be within the range of incidence reported in the abovementioned countries (Chen et al, 2013). However, the method used to estimate the burden of foodborne disease in the United States, England and Wales and Australia was different from that in China.…”
Section: Introductionmentioning
confidence: 95%